An Investigation on The Cooperative Maxims in D.H. Lawrence’s Short Story of the “Rocking Horse Winner” - Suswanto Ismadi Megah; Sri Sugiharti; Mulva Dessa Ariesti; Tri Artanto; Zulida Abdul Kadir; Saira Kazmi (Journal of Pragmatics Research, 2024)
This study aimed to investigate main issue of the maxims used in the short story The Rocking Horse Winner by DH Lawrence is a story that tells the story of a woman, Hester's dissatisfaction with her family's economic situation which triggers other problems. This study contributes in improving pragmatic study, particularly cooperative maxims used to identify how certain type applied in daily communicative realized inside the Short Story of the “Rocking Horse Winner”.  Basically, this research is qualitative. The type of research that focuses on "humans: interpersonal relationships, personal values, meanings, beliefs, thoughts, and feelings. The use of quantitative data to strengthen the tendency of one type of maxims in order to get a better result explanation. Therefore, in this study, the researchers analyze the type and level of frequency of the cooperative maxim contained inside the data. In conducting this research, the researchers applied the four cooperative maxims in analyzing the data found.  The four maxims such Maxim of quality, quantity, relationship and manner. This research found that the maxim of relationship dominates the dialogue part of the story. Other maxims are also found in small numbers. Therefore, It has been concluded that the maxim of relation came to the highest portion compared to the others. It showed that. The main character of the short story attempts to have an excellent way to interact with others. This was utilized to receive the message well and positively impact their life.